PRACTICAL STATE OF REMOTE BANKING SERVICES BY COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2024)
The article deals with the problems of improving the remote banking services of republican commercial banks - scientific recommendations for improving the quality of remote banking services in commercial banks and ensuring the timely repayment of online loans, expanding their scope based on the study and analysis of the state of remote banking services and improving remote banking services based on continuous study of customer opinions developed and formed conclusions. The level of use of information and communication technologies is expanding in all areas around the world.